ХИРУРШКИ ТРЕТМАН НА ТУМОРИ НА НАДВОРЕШНАТА ПОВРШИНА НА НОСОТ – НАШЕ ИСКУСТВО - Маре Стевковска; Грета Марцикиќ; Добрила Андоновска; Емилија Атанасова; Елизабета Oбочки; Мира Ѓорчева; Билјана Шaпова; Јасна Угриновска; Елисавета Томова (SHMSHM / AAMD, 2012)
The external surface of the nose is crossed by ridges and valleys that separate it into slightly convex or concave surfaces. The nose is an aesthetic unit of the face and the surgeon should be aware of both the topographic and the internal anatomy of the nose before proceeding with any reconstructive procedure. Goal: To review nasal reconstruction over 4 years ( 2006-2009) at the University Surgical Clinic "Sv. Naum Ohridski" Skopje, Macedonia, at the Department of Plastic and Aesthetic Surgery . Material and Methods: 70 cases underwent surgery for tumors of external surface of the nose between 2006 and 2009: Female 33 (47%), Male 37( 53%), average age 40- 81 years old; with the nasal reconstruction options (under local or general anesthesia): simple suture close 5 cases (7%) , secondary intention healing 2 cases (3%), skin grafting 12 cases ( 17%), local flaps 47 cases ( 67% ) and regional flaps 4 cases (6%) Results: Tumors of the external surface of the nose are basal in 62 cases (89%) and squamous cell skin cancers in 8 cases (11%), with localization: radix nasi 15 (21%), dorsum nasi 44(63%), apex nasi 8 (12%), alae nasi 2 (3%), columella nasi 1(1%), Nasal reconstructive procedures can be safe and effective with proper training, patient selection, surgical planning, and operative technique. Few complications are associated: operative site bleeding, hematoma formation 2 cases (3%), wound infection at 5 cases (7%), tissue necrosis at 2 cases (3%), and non adequate tumor removal (recurrent basal cell carcinoma) at 4 cases (6%), and 1 (1%) patient without aesthetic satisfactory result. The sutures are removed within 10-14 days. Conclusion: Defects vary in site, size, shape, depth. A large variety of sophisticated techniques continue to emerge with the goal of producing increasingly natural results for patients. Key words: Nose, tumor, reconstruction, flap
SURGICAL TREATMENT OF TUMORS OF THE EXTERNAL SURFACE OF THE NOSE
Keywords: нос; тумори; реконструкција; резен